The peculiarities of 90SR accumulation in ukrainian polissya soils long after chernobyl disaster - Романчук, Л. Д. (Scientific Progress & Innovations, 2012)
The paper presents the results of the investigation of the soil contamination density of 90Sr in Zhytomyr district which is classified as a radionuclide – free territory as in Korosten and Narodychi districts which suffered as a result of the Chernobyl disaster. Our investigations proved that the density of 90Sr and 137Cs fallout in the districts of the Northern Ukraine testify to considerable differences in the contamination levels. Thus, the contamination density in Zhytomyr district was on on average 1,4 kBq/m2, and in Narodychi district the density reached 30,3 kBq/m2.